PAN-GERMANISM AND THE EMERGENCE OF NATIONAL-SOCIALIST IDEOLOGY - KOSYAK, S. M. (Вісник Черкаського університету. Серія: Історичні науки, 2017)
In article analyzes the basic ideas and theoretical positions Pan-Germanism, a theory that emerged in the 80s of XIX century in Germany and took shape an integral ideological doctrine at the end of XIX-beginning of the XX century. Author presented characteristics of relevant researches of scientists-Germanists regarding the features of formation of Pan-Germanism theoretical principles and factors which influenced on this process. This issues studied by foreign and domestic scholars (A. Abush, G. Halharten, V. Dayst, A. Dunn, A. Pehushev, A. Balyezin, Yu. Rudakov, К. Tsymbayev, E. Puhovska, S. Fokin, S. Troyan. The essence and the reasons expansionist policy of Germany in the second half of the XIX century investigated in researches of these authors. In this scientific article the author investigated the genesis of expansionist ideas of the German Empire under the influence of internal and external factors. The researcher justifies the logic and natural origin and development of theoretical principles (ideas) Pan-Germanism as geopolitical ideology. For substantiation of its reasoning the author used the works of ideologists of Pan-Germanism such as G. Shoner, F. Ratzel, R. Сhellen, Karl Haushofer The author focused on the development of German scientists and politicians basic principles of the idea of creating a «Middle Europe» and the role of Germany as an axial state in the European association. The author also investigates the origin, under the influence of foreign factors, one of the areas of Pan-Germanism – ariosophy, which was founded by H. Chamberlain. He was one of the first who declared the need to create a «pure race», referring to the same German nation. The political interpretation of «racial purity», which based on biological determinism, gave in his works L. Voltman. He explained and classified the political ability of certain races, which brought on the basis of regularities in the formation of states. Thus, it was found that exactly the idea of Pan-Germanism laid the foundation for the formation of the ideology of German National Socialism that will be the state in Germany in the days of Adolf Hitler and make possible the outbreak of the Second World War.